Ergonomic Exercise Against Elderly Functional Capabilities - Ngo, Ly (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze the effect of ergonomic exercise on increasing the functional ability of the elderly in posyandu who have decreased ability to help. The design of this study used a quasi-experimental method with pre-test and post-test techniques without a comparison (control) group. The results showed that there was an increase in the value of functional ability with p-value = 0.000 <0.05. In conclusion, ergonomic exercise therapy has an effect on increasing helping capacity in the elderly. Keywords: Elderly, Functional Ability, Ergonomic Gymnastics